Wage Adjustment and Productivity Shocks. (29th June 2015) - Carlsson, Mikael; Messina, Julián; Skans, Oskar Nordström
Abstract : We study how workers' wages respond to changes in firm‐level physical productivity using Swedish data. We find that technology shocks affect workers' wages through both internal and external forces. Wages respond three times as much to physical productivity shocks that are shared with outside firms within the same sector as they do to firm‐level physical productivity shocks. The larger impact of sectoral physical productivity is related to the degree of within‐sector labour mobility, suggesting that the productivity evolution among firms that draw their labour from the same market segment is a crucial determinant of the wage growth of incumbent workers.